2002
DOI: 10.1086/341302
|View full text |Cite
|
Sign up to set email alerts
|

Injection Drug Use Facilitates Hepatitis C Virus Infection of Peripheral Blood Mononuclear Cells

Abstract: Infection of peripheral blood mononuclear cells (PBMCs) with hepatitis C virus (HCV) has been demonstrated and has been found to play a role in relapse of HCV disease and vertical transmission of HCV. Injection drug use is thought to impair function of the immune system and induce tolerance to viruses; therefore, HCV infection of PBMCs could be more likely to occur in injection drug users (IDUs) with HCV infection. Of 108 women who tested negative for human immunodeficiency virus type 1 and positive for HCV RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…This effect may be due to concentration differences, but may be due to other undetermined factors. A study of HCV-positive intravenous drug users (IDU) showed that they were more likely to have negative strand in PBMC than non-IDU HCV-positive patients [31]. This was most likely due to the state of their immune systems, but could be due to other factors such as time after infection.…”
Section: Hcv Can Bind and Enter Extrahepatic Cellsmentioning
confidence: 99%
“…This effect may be due to concentration differences, but may be due to other undetermined factors. A study of HCV-positive intravenous drug users (IDU) showed that they were more likely to have negative strand in PBMC than non-IDU HCV-positive patients [31]. This was most likely due to the state of their immune systems, but could be due to other factors such as time after infection.…”
Section: Hcv Can Bind and Enter Extrahepatic Cellsmentioning
confidence: 99%
“…The association between intravenous drug use and vertical transmission also persisted in past and present users. The authors suggest that the mechanism for increased transmission may be due to a higher incidence of hepatitis C in peripheral blood monocytes of intravenous drug users with hepatitis C [26]. They also argue that prior studies were unable to tease out this association because most studies did not include adequate numbers of women who were HIV positive and not intravenous drug users.…”
Section: Intravenous Drug Usementioning
confidence: 99%
“…Vertical HCV transmission occurs only from mothers whose PBMCs harbor the virus. We recently showed that PBMCs infection by HCV is significantly more frequent in IDU-positive women than in other HCV-positive women [6]. In fact, HCV RNA was demonstrated in PBMCs obtained from 33 of 51 IDU-positive women and from 13 of 57 control women ( …”
Section: Replymentioning
confidence: 99%
“…HIV-1 IIIB is a T-tropic strain that predominantly uses the CXCR4 coreceptor [5]. Recent reports suggest that HIV coreceptors and HIV-1 fusion are differentially regulated in CEM cells, compared with primary lymphocytes, suggesting that these cells may not be the optimal surrogate for infectivity assays [6]. To investigate the validity of using cell lines that have been selected for drug resistance, we have examined the expression of HIV receptors in CEM, VBL 100 , and E 1000 cells.…”
Section: Differential Expression Of Human Immunodeficiency Virus Corementioning
confidence: 99%